Systematic literature review of integrated project scheduling and material ordering problem: Formulations and solution methods. (November 2022) - Parchami Afra, Ali; Kheirkhah, Amirsaman; Ahadi, Hamidreza
Highlights: Reducing the total cost by integrating project scheduling and material ordering. Review of articles in accordance with the systematic literature review approach. Identification of the findings of the reviewed articles. Presentation of literature review results based on a specific classification scheme. Providing suggestions for future research fields. Abstract: Project cost performance and resource availability can be improved by integrating project scheduling and material ordering. Integrating project scheduling and material ordering can achieve an optimal total cost due to trade-offs among project cost elements such as material purchase costs, availability of renewable resources, and ordering and holding material. Several studies in the project scheduling literature have addressed project scheduling and material ordering problems with varying assumptions and characteristics and have formulated these problems using mathematical models. This paper reviews studies that modeled and solved these integrated problems using a systematic literature review approach. The systematic literature review seeks to provide evidence to answer research-specific questions such as 1) Under what assumptions and conditions have the integrated project scheduling and material ordering problems been studied? 2) How are these problems formulated, and what mathematical models are proposed? 3) What methods are used to solve the mathematical models? 28 articles were eventually chosen during the search process steps. The selected articles were reviewed and presented using a classification scheme that consists of five aspects: project scheduling problem type, material ordering aspects, uncertainty conditions, objective function, and solution method. The mainstream of research in this scope is identified based on the article review results; thus, future research fields can be identified. This paper provides authors who want to research in this area with insights into the formulation of problems and solution methods, as well as information from previous articles.